Tannins of tamarind seed husk: Preparation, structural characterization, and antioxidant activities - Puksiri Sinchaiyakit (2018)
The high content (about 39%) of polymeric tannins in tamarind (Tamarindus indica L.) seed husk (TSH) was demonstrated, and an extract (crude TSE) with a high content (about 94%) of polymeric tannins was prepared from TSH with a one pot extraction using ethanol/water (3:2, v/v). The crude TSE was further purified with Sephadex LH20 to give one fraction (metTSE) eluted with methanol/water (3:2, v/v) and another (acTSE) eluted with acetone/water (3:2, v/v). The tannins of acTSE were established as polymeric proanthocyanidins (PA) by 13C NMR spectroscopy; this was further confirmed by IR and UV spectroscopy, n-BuOH/HCl and vanillin assays, and from HPLC pattern. The ratio of procyanidins to prodelphinidins was 2:3, and the average degree of polymerization of acTSE was 7. Galloylated flavan-3-ols were not detected in acTSE. The main ingredients of metTSE were confirmed to be polymeric PA by 13C NMR spectroscopy. The antioxidant activities using DPPH and ABTS assays were investigated. The IC50 values of acTSE were 4.2±0.2 (DPPH assay) and 6.2±0.3 μg/mL (ABTS assay).